The importance of managerial skills in the implementation of the regional bulk infrastructure grant in Mopani District Municipality, Limpopo Province South Africa - Selane, Lebogang Salome (My University, 2021)
Local government is seriously affecting governance due to lack of leadership, management, technical skills and knowledge within government. Shortage of skills is a continuous challenge at district level and in skills development activities despite considerable expenditure on skills development. The district officials are compromised because human resource development directorates have poorly planned effective training. The Local Government Municipal Systems Act (South Africa, 2000) relating to municipalities state that staff development is important for effectiveness and efficiency in compliance with legislation and enabling the performance of functions. The above challenges have stimulated the researcher to embark on this research. The study was aimed to investigate the importance of managerial skills in the implementation of the Regional Bulk Infrastructure Grant in Mopani District Municipality, Limpopo Province.The study determined the managerial skills possessed by officials, attempted to understand how the officials in Mopani District Municipality manage the implementation of the Regional Bulk Infrastructure Grant. The study further explored training programmes that can equip municipal officials with managerial skills. Mopani District Municipality has a mandate as the local government to service communities. National Treasury funds the Regional Bulk Infrastructure Grant; usage of the grant must be accounted for, regulations and frameworks guide its implementation. An overview of Water Infrastructure development by the Deputy Director-General NWRI from the Department of Water Affairs, shows that there are 27 District including MDM that are allocated the Regional Bulk Infrastructure Grant for the new infrastructure development, refurbishment, for the ageing infrastructure to be upgraded and replaced and extensive areas across municipal boundaries to be serviced. The Department of Water Affairs report indicates that due to delays in the procurement of material, engineering new appointments and other services, projects for 2017/18 financial year in Limpopo province have been delayed to the 2018/19 financial year. The research approach that was used in this study is qualitative research because it enables the researcher to critically investigate the importance of managerial skills in the implementation of the Regional Bulk Infrastructure Grant in Mopani District Municipality, Limpopo Province. The study employed both interviews and questionnaires for data collection. The interview was done at Mopani District Municipality and Mopani Community (Beneficiary) were given semi-structured questionnaires. The findings reveal that officials in Mopani District Municipality do not possess business skills. The officials that are trained received either traditional or competencybased training and do not possess managerial skills for implementation of RBIG. The study further noted that Mopani District Municipality is no longer an implementing agent due to the challenges the district encountered. The project had challenges that made the project not being completed within a stipulated period which was 2018. The Department of Water Affairs appointed Lepelle Northern Water as RBIG implementing agents due to the above challenges. Based on the findings, the following recommendations were made to Mopani District Municipality officials: • The district Human Resource Development office must afford officials training prior to being appointed. The HRD must conduct a skills audit to be able to know which officials need skills development. • Department of Water Affairs, Lepelle Northern Water and Mopani District Municipality must forge good intergovernmental relations ensuring that end service is delivered to residents. • Mopani District Municipality must partner with the University of Limpopo, University of Venda, Tshwane University of Technology, University of South Africa and so forth for providing effective traditional training.
Thesis (MBA.) -- University of Limpopo, 2021
Keywords: Local government; Managerial skills; Leadership; Technical skills; Infrastructure (Economics); Local government -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo; Leadership -- South Africa -- Limpopo